The Settlement of Credit Due to Death - Soegianto Soegianto; Sukarmi Sukarmi (Jurnal Akta, 2021)
The debt burden is given to the heirs who are willing to accept the inheritance in full. The amount of the debt itself will be adjusted to the size of the inheritance received, outside of his own personal property. Of course, this debt shift will be a heavy burden. Especially if your own needs are already heavy. If indeed you are experiencing these problems, the methods below can help to pay off debts from deceased debtors. This research aim to: 1) To identify and analyze the implementation of the settlement of non-performing credits are collateralized with mortgage collateral while the owner died. 2) To identify and analyze the role of the Notary of the Installation Encumbrance with Certificate Name Properties that have made the process dies down to the Expert Heir based Justice. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analysis method. Based on the results of data analysis concluded that: 1) the implementation of the settlement of non-performing credits are collateralized with mortgage collateral while the owner died. 2) the role of the Notary of the Installation Encumbrance with Certificate Name Properties that have made the process dies down to the Expert Heir based Justice.